Synergy of Technology and Agriculture through the Development of a Web-Based Expert System for Cocoa Disease Diagnosis Using the Certainty Factor Method - Kevin Yanto; Musdalifa; Moh Ali Akbar A Dg Matona; Juni Wijayanti Puspita (School of Computing, Telkom University, 2025)
Cocoa (Theobroma cacao L.) is one of the leading agricultural commodities that plays a vital role in Indonesia’s economy. However, its productivity is often hindered by pest and disease attacks. On the other hand, the limited availability of agricultural experts and the difficulties faced by farmers in accessing guidance and information regarding plant diseases highlight the urgent need for a system that can assist in identifying problems quickly and accurately. This study aims to develop a web-based expert system capable of diagnosing pests and diseases in cocoa plants using the Certainty Factor (CF) method. The system incorporates data on 9 types of diseases and 6 types of pests along with their symptoms. Diagnosis is performed by calculating certainty values based on a combination of expert confidence and user input using CF formulas. With a web-based interface, the system can be easily accessed by farmers via the internet. The diagnostic results of this system show a similarity rate of 93.33% with those of other studies. This finding indicates that the CF approach demonstrates competitive performance. Therefore, this system has the potential to serve as an effective tool in supporting cocoa plant health management by farmers.Keywords: Disease diagnosis, Cocoa, Certainty factor method, Web-based expert system